2022
DOI: 10.1029/2022gl100067
|View full text |Cite
|
Sign up to set email alerts
|

Cloud‐Radiation Feedback Prevents Tropical Cyclones From Reaching Higher Intensities

Abstract: The prediction of tropical cyclone (TC) intensity remains a major scientific challenge. Recent studies indicate that cloud‐radiation feedback (CRF) plays a positive role in the intensification of TCs during their genesis. However, little attention has been given to how CRF affects TC intensity after genesis. This study shows that CRF may prevents TCs from attaining higher maximum intensities. The ascending motion induced by the anomalous radiative heating of TC promotes more latent heating on the outer side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Meanwhile, a secondary RMW takes place at an 80‐km radius after 36 hr and contracts radially inward to the 60‐km radius, indicating an SEF in CTRL. By comparison, in NRAD48, V max is larger than that of CTRL, implying that CRF could prevent the storm from reaching higher intensity (Yang et al., 2022). Although there is a slight intensity fluctuation after 36 hr, there is no secondary RMW nor SEF in NRAD48, indicating the removal of CRF inhibits SEF.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a secondary RMW takes place at an 80‐km radius after 36 hr and contracts radially inward to the 60‐km radius, indicating an SEF in CTRL. By comparison, in NRAD48, V max is larger than that of CTRL, implying that CRF could prevent the storm from reaching higher intensity (Yang et al., 2022). Although there is a slight intensity fluctuation after 36 hr, there is no secondary RMW nor SEF in NRAD48, indicating the removal of CRF inhibits SEF.…”
Section: Resultsmentioning
confidence: 99%
“…Previous modeling studies suggested that the strengthening of TCs due to a warmer sea surface temperature would be counterbalanced by the stabilization of the troposphere under warming 35 . Yet, these studies did not account for cloud-radiative feedback, an element underscored by recent research for its pivotal role in enhancing TCs [36][37][38][39] . The changes in the convective core size and organization might stem from enhanced cloud-radiative feedback under warming.…”
Section: Scale-dependent Sensitivity: Storm Organization Changesmentioning
confidence: 99%